Enhancing preventive maintenance using data mining technique - Loh, Wei Cheng. (2010)
Maintenance is an important part in any operational system, keeping equipment in good condition. This report proposed a maintenance model, multi criterion decision making grid (DMG), to provide decision support for different components and parts in equipment, applicable in both single and multi-unit system. The author will then attempt to apply this model to an industrial case study, using deterministic criterion gathered from the case study historical data in making this decision analysis. Decision support capability of the model is further improved by employing fuzzy inference system (FIS). Discussion and implementation of fuzzy logic would also have to be made. Also, a simplify data performance analysis is presented with the decision making grid model.